Pattern of Spatial and Temporal Variations of Rainfall in the Northern Province of Sri Lanka, 1972 - 2014 - Piratheeparajah, N. (Indian Society of Spatial Scientists, 2016)
Survival of every species in a place is controlled by weather factors. Rainfall is the important weather parameter that influences all sectors of the economy of the study area viz the Northern Province of Sri Lanka. Rainfall pattern of the study area varies from other regions of Sri Lanka. In this respectthisstudyfocusesonthetrendanddistributionoftherainfallinthestudyarea.Themain objective of this paper is to discuss the spatial and temporal pattern of the rainfall in the northern province of Sri Lanka. Primary data were collected using direct observation, which helped to identify thespatialvariationsoftherainfallofthestudyarea.Secondarydatawerecollectedmainly from two sources i.e Department of Meteorology and the Statistical Handbook of the Northern Provincial Council. Data related to rainfall from department of meteorology were collected for forty-four years from 1972 for the analysis. Data have been analyzed using excel worksheet and they were mapped using the ARC GIS software 9.1 version to identify the temporal and spatial patternoftherainfallinthestudyarea.Annualaveragerainfallofthestudyareavariesfromyearto year. SeasonallySecondInterMonsoonSeasonandtheNorthEastMonsoonSeasonreceive85%of rainfall and South West Monsoon Season receives 17% of rainfall. The Months, November, December and January receive 90% of the total rainfall. Spatially eastern part of the study area receives the highest amount of rainfall and the western area receives the lowest amount of rainfall. Number of rainy days decrease year by year and the depression in the Bay of Bengal is the main reasonforthe92%ofthetotalrainfallofthestudyarea.
Keywords: Rainfall; Northern Region of Sri Lanka; Spatial Pattern; Temporal Variation; Seasons